Is This a Word for an Emotion? Considering a Set of English Data - Tisari , Heli (International Journal Linguistics of Sumatra and Malay, 2022)
There are many words that rather clearly denote emotions, such as the nouns anger, happiness, and sadness. However, some cases are not so clear. For example, if a person feels relaxed, the adjective can refer to a physiological as well as an emotional state. It may be even more difficult to decide if a word such as the noun fun or the adjective warm refers to an emotional state. In this paper, I will discuss a list of 86 words that I collected while annotating a set of British English texts. They consisted of people’s fond memories of the music of digital games, and I aimed to mark all words that referred to emotions. I made notes of words that I was uncertain about. Here, those words are considered in the light of two dictionaries, the Macmillan English Dictionary for Advanced Learners, and the Oxford English Dictionary online.